Re-constructing the political mindset of the persian gulf security - Henelito A. Sevilla, Jr., (Institut Kajian Rantau Asia Barat, 2011)
Persian Gulf region is one of the most strategically important regions in the world. The presence of its large oil and gas reserves coupled with some of its most vital water routes to international movement of merchandises would require well coordinated and transparent policies by which all littoral states including other regional and extra- regional state actors should actively involve. In order to maintain the free movements of oil and other commodities, it is necessary that the security of the Gulf is stable. This article examines security perceptions and priorities of the littoral states of the Persian Gulf region. Longstanding mistrust, foreign intervention as well as varying national priorities which prevent them from reaching consensus to establish a stable collective security. Finally, the article recommends that there is a need to re-construct the political mindset of Persian Gulf security so everyone can enjoy the benefits the region offers to humanity.